3D inversion of irregular gridded 2D electrical resistivity tomography lines: Application to sinkhole mapping at the Island of Corfu (West Greece) - Kim, Jung-Ho; Tsourlos, Panagiotis; Karmis, Petros; Vargemezis, George; Yi, Myeong‐Jong (Near surface geophysics (Online), 2016)
ABSTRACT We study the case of the combined interpretation of irregularly gridded 2D electrical resistivity tomography lines. A 3D inversion algorithm was specially modified to accommodate the full 3D processing of such lines. The chosen approach uses a dense structured mesh and a flexible parameter design scheme. Tests with synthetic data show that full 3D inversion results are significantly improved when compared with the equivalent quasi‐3D imaging of the 2D inversion results. It is also shown that 3D inversion results can provide correct location and shape information about targets that are not directly located under the measured lines. The scheme was tested with real data from a site in the northern part of the Corfu Island (West Greece) where a large number of irregular gridded 2D electrical resistivity tomography lines were collected in order to map sinkholes related to gypsum. The 3D inverted images provide important information about the structure of the existing sinkholes and the potential sinkhole generation mechanism. Overall, the possibility of 3D interpretation of irregularly gridded lines is not only important for obtaining better subsurface images but also allows a more flexible and practical design of electrical resistivity tomography field surveys.